2022
DOI: 10.1038/s41591-022-01969-y
|View full text |Cite
|
Sign up to set email alerts
|

A real-world comparison of tisagenlecleucel and axicabtagene ciloleucel CAR T cells in relapsed or refractory diffuse large B cell lymphoma

Abstract: Axicabtagene ciloleucel (axi-cel) and tisagenlecleucel (tisa-cel) have both demonstrated impressive clinical activity in relapsed/refractory (R/R) diffuse large B cell lymphoma (DLBCL). In this study, we analyzed the outcome of 809 patients with R/R DLBCL after two or more previous lines of treatment who had a commercial chimeric antigen receptor (CAR) T cells order for axi-cel or tisa-cel and were registered in the retrospective French DESCAR-T registry study (NCT04328298). After 1:1 propensity score matching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
124
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(192 citation statements)
references
References 37 publications
16
124
5
Order By: Relevance
“…The overall CRS incidence was higher after axi-cel than after tisa-cell (86.1 vs. 75.6%), but the severe CRS incidence was similar (9.1 vs. 5.3%); in addition, the overall and severe ICANS incidences were higher after axi-cel than after tisa-cel (48.8 vs. 22 and 13.9 vs. 2.9%, respectively), as was the rate of cytopenia. The ORR and CR rate were significantly higher for the axi-cel group than for the tisa-cel group (80.4 vs. 66 and (33). These data confirmed the initial results from the matching adjusted indirect comparison (MAIC) trial (37).…”
Section: Results After Car-t-cell Therapy In Lbclsupporting
confidence: 82%
See 2 more Smart Citations
“…The overall CRS incidence was higher after axi-cel than after tisa-cell (86.1 vs. 75.6%), but the severe CRS incidence was similar (9.1 vs. 5.3%); in addition, the overall and severe ICANS incidences were higher after axi-cel than after tisa-cel (48.8 vs. 22 and 13.9 vs. 2.9%, respectively), as was the rate of cytopenia. The ORR and CR rate were significantly higher for the axi-cel group than for the tisa-cel group (80.4 vs. 66 and (33). These data confirmed the initial results from the matching adjusted indirect comparison (MAIC) trial (37).…”
Section: Results After Car-t-cell Therapy In Lbclsupporting
confidence: 82%
“…The patient characteristics were well balanced, and while the ORR, duration of response (DOR), PFS and OS were not significantly different between the treatments, the incidence of ICANS was higher while the CRS rate was similar after axi-cel ( 32 ). Different findings were reported in the second study ( 33 ), in which a large number of patients included in the DESCART national registry were analyzed (209 who received tisa-cell vs. 209 who received axi-cel) using propensity score matching to reduce differences in variables associated with outcomes. The overall CRS incidence was higher after axi-cel than after tisa-cell (86.1 vs. 75.6%), but the severe CRS incidence was similar (9.1 vs. 5.3%); in addition, the overall and severe ICANS incidences were higher after axi-cel than after tisa-cel (48.8 vs. 22 and 13.9 vs. 2.9%, respectively), as was the rate of cytopenia.…”
Section: Results After Car-t-cell Therapy In Lbclmentioning
confidence: 82%
See 1 more Smart Citation
“…Approximately 57% of patients with r/r DLBCL experience disease progression or relapse after autologous 19CAR-T cell therapy [31,32]. For example, early disease progression within 30 days or after 30 days has been reported to have a median OS of 3.75 months and 9.28 months, respectively [33].…”
Section: Introductionmentioning
confidence: 99%
“…A comparison of axi-cel versus tisa-cel in R/R DLBCL patients was recently reported using real-life data from the French registry for commercial CAR T-cell therapy (DESCAR-T). 18 Stringent 1:1 propensity scores (PS)-matching (n=418) demonstrated that patients receiving axi-cel versus tisa-cel had higher response rates (ORR: 80.4% vs 66.0%, CR rate: 60.3% vs 42.1%; p<0.001) at a 1-year median follow-up. Furthermore, axi-cel compared with tisa-cel significantly extended PFS (median, 8.2 months vs 3.1 months, HR: 0.61 [95% CI: 0.46-0.79]; 0.0003) and OS (median, not reached vs 11.2 months; HR: 0.63 [95% CI: 0.45-0.88]; p=0.0072) (Figure 1).…”
mentioning
confidence: 99%